The Use of References in English News Published by Jakarta Post and New York Time Online Newspaper - Muhimatun Asroriyah, Atik (English Education and Literature Journal (E-Jou), 2021)
This study highlights the use of references in the element of cohesive devices in English news article of The Jakarta Post and New York Time written by Indonesian non-native and American native. The purpose of this study is to identify the similarities and differences in using personal references, demonstrative references and comparative reference. The method of this study is descriptive qalitative. The data were taken from online newspaper; The Jakarta Post and New York Times articles. There are 20 articles which are analyzed in this study, 10 articles from each online newspaper in any field of these newspaper. The data were analyzed use (Halliday and Hasan’s : 1976) the theory of cohesion. The result of this study explained that the use of references in the New York Time articles higher than The Jakarta Post articles. The most dominant use the type of reference is personal reference both of the articles.